How HIV/AIDS health education boosts high school students’ knowledge - Anggraini, Lutfi; Rokhanawati, Dewi (Universitas 'Aisyiyah Yogyakarta, 2025)
The incidence of HIV/AIDS continues to rise. The high number of cases among adolescents is due to their lack of knowledge and attitudes about HIV/AIDS, which directly affects the prevention of this disease. Knowledge about HIV/AIDS is considered crucial, as it plays a role in shaping public perceptions, thereby influencing their understanding and awareness. HIV/AIDS health education for adolescents can be an effective approach to developing their knowledge about reproductive health and sexually transmitted diseases. This study aims to investigate the impact of HIV/AIDS health education on the knowledge level of 11th-grade students at SMA Negeri 1 Pundong. This study employed nonequivalent pretest-posttest control group design. The sampling technique used was probability sampling, with a total of 32 respondents divided into an experimental group of 16 and a control group of 16. Data were analyzed using non-parametric tests: the Wilcoxon matched-pairs test and the Mann-Whitney U test. Based on the pretest and posttest results, the average knowledge score in the experimental group increased from 60.69 to 83.00, while in the control group it rose from 63.70 to 73.00. The analysis showed a significant difference in knowledge levels before and after the HIV/AIDS health education intervention in both the experimental and control groups, with a p-value of 0.004 (p < 0.05). This study concludes that HIV/AIDS health education has a significant effect on improving the knowledge of 11th-grade students at SMA Negeri 1 Pundong.